IgYs: on her majesty’s secret service - Grzywa, Renata; Łupicka-Słowik, Agnieszka; Sieńczyk, Marcin (Frontiers in Immunology, 2023)
There has been increasing interest in using IgY antibodies as an alternative to ‘classical’ antimicrobials. Unlike traditional antibiotics, they can be utilized on a continual basis without leading to the development of resistance. The veterinary IgY antibody market is growing due to the demand for minimal antibiotic use in animal production. IgY antibodies are not as strong as antibiotics for treating infections, but they work well as preventative agents, are natural, nontoxic, and easy to produce. They can be administered orally and are well tolerated, even by young animals. Unlike antibiotics, oral IgY supplements support the microbiome that plays a vital role in maintaining overall health, including immune system function. IgY formulations can be delivered as egg yolk powder and do not require extensive purification. Lipids in IgY supplements improve antibody stability in the digestive tract. Given this, using IgY antibodies as an alternative to antimicrobials has garnered interest. In this review, we will examine their antibacterial potential.